Pengaruh layanan penguasaan konten terhadap meningkatnya kecerdasan interpersonal siswa di SMA Bina Bangsa Mandiri Cikeas Bogor - Christine Masada Hirashita Tobing; Aena Susilawati; Mulyadi Mulyadi (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
The development of interpersonal intelligence is needed because individuals in daily life need each other with others. One of the effective guidance and counseling services to improve interpersonal intelligence is content mastery services. The purpose of this study is to prove the effect of content mastery services on increasing interpersonal intelligence of students in high school. The method used is an experimental research method, using The Non-Equivalent Group Design. This study uses purposive sampling with 72 students as the subject of research where 36 students will be used as the experimental group and 36 students will be used as the control group. Based on the results of the pretest the value of the two groups approached comparable where the value of the experimental group was slightly lower than the value of the control group. The posttest results showed a significant difference where the value of the experimental group given the treatment was higher than the value of the control group that was not given the treatment. The conclusion is that there is an influence of content mastery service on increasing students' interpersonal intelligence